Life cycle optimisation of a sustainable sago value chain - Wan, Yoke Kin (Animo Repository, 2014)
In line with global concern on the sustainable development, economic, environmental and social aspects should be considered simultaneously in an entire value chain. In this work, a cradle-to-gate life cycle optimisation (LCO) of sago value chain that involves plantation, harvesting and processing of sago starch as well as transportation of sago starch to customer is developed. In addition, fuzzy optimisation is adapted to minimise both total operating cost and workplace footprint of sago value chain. Note that in this work, the workplace footprint is divided into three levels of risk which are death (D), non-permanent disability (NPD) and permanent disability (PD) risks. These risks and operating cost are considered simultaneously and traded off to identify the optimum pathway with minimum risks as well as operating cost for sago value chain. A realistic case study is solved to illustrate the developed approach. Copyright © 2014, AIDIC Servizi S.r.l.